Impairments in Activities of Daily Living in Older Japanese Men in Hawaii and Japan - Robert D. Abbott; Aya Kadota; Katsuyuki Miura; Takehito Hayakawa; Takashi Kadowaki; Tomonori Okamura; Akira Okayama; Kamal H. Masaki; Hirotsugu Ueshima (Journal of Aging Research)
Introduction. Hypertension and cigarette smoking are dominant risk factors for cardiovascular disease in Japan while in westernized countries, broader effects encompass obesity, diabetes, and hypercholesterolemia. This paper examines whether different associations also appear important in the manifestation of activities of daily living (ADL) in older Japanese men in Hawaii and Japan. Methods. Measures of ADL (feeding, toileting, dressing, bathing, and walking around the house) were assessed from 1995 to 1999 in 1,893 men in Hawaii and 543 men in Japan. Concomitant risk factors were measured from 1990 to 1993. Results. In Hawaii, diabetes increased the odds of ≥1 ADL impairment nearly 1.5-fold (P=.020). A similar association was absent in Japan. In contrast, the odds of an ADL impairment in Japan was increased more than 5-fold in the presence of stroke (P<.001). The association in Hawaii was significantly weaker (P=.007). In both cohorts, past alcohol use was associated with a greater likelihood of ADL impairment. Conclusion. In this comparison of genetically similar samples, findings suggest that different strengths in risk factor associations with cardiovascular disease in Japan and westernized countries may also include different strengths in associations with impaired ADL.